Optimal Design Parameters of a Percussive Drilling System for Efficiency Improvement - Changheon Song; Jintai Chung; Jae-Sang Cho; Yun-Joo Nam (Advances in Materials Science and Engineering)
This paper aims to determine the optimal design parameters for percussive drilling systems considering the bit-rock interaction. First, the motion dynamics of a bit impacted by a dropped piston are modeled by impact stress propagation and a rock-breaking mechanism representing the penetration resistance coefficient and unloading constant. Next, the damping vibration behavior of the bit is investigated considering the impact duration and the rock loading/unloading condition. In addition, the proposed dynamics are simplified by adopting two dimensionless parameters representing the bit-piston mass ratio and the rock-piston stiffness ratio. Finally, the drilling efficiency, defined by the energy transmitted from the piston to the rock, is presented in terms of the proposed parameters. The use of optimal design parameters for percussive drilling systems improved the drilling efficiency. These results are applicable to the design and performance estimation of down-the-hole and top-hammer systems.